Pengalaman Pedagogis Guru dalam Mengatasi Kesulitan Belajar Siswa pada Pembelajaran IPAS di Sekolah Dasar - Latifa Ruliandari; Yantoro; Issaura Sherly Pamela (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The implementation of Natural and Social Sciences (IPAS) learning in the Independent Curriculum faces challenges in the form of differences in student learning abilities that make it difficult for teachers to realize learner-centered learning. This study aims to describe teachers' pedagogical experiences in overcoming student learning difficulties in IPAS learning. The study used a qualitative approach with a phenomenological design and was conducted in three elementary schools in Batang Hari Regency, Jambi Province, Indonesia. The study participants consisted of fifth-grade teachers who were purposively selected based on their experience teaching IPAS. Data were collected through in-depth interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that teachers' pedagogical experiences are reflected in three main stages: planning, implementation, and evaluation of learning. Teachers overcome student learning difficulties through the application of contextual learning, the use of learning media, peer tutoring, group discussions, and individual mentoring. Reflection on the learning process plays an important role in helping teachers refine learning practices to be more responsive to students' learning needs.